2006
DOI: 10.1021/ie050363d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on Fluoride Removal by Calcined Layered Double Hydroxides

Abstract: The layered double hydroxides (LDHs) calcined at a certain range of temperature have the “memory effect” which means to recover its original layered structure in the presence of appropriate anions. Kinetics of fluoride removal from aqueous solution by calcined MgAl−CO3 LDHs (denoted CLDH) was studied in batch mode. The influences of pH of solution, initial fluoride concentration, CLDH quantity, and temperature on the kinetic of fluoride removal have been tested in detail. The results of four kinetic models fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 33 publications
3
43
2
1
Order By: Relevance
“…By example, Barboza et al [5] and [12] reported values of the Biot in the range of 30 ~ 50 for the adsorption of CA into synthetic resin Amberlit IRA 400. Other authors have related Bi 100 with external mass transfer resistance as a limiting step [17,18]. In this present work, the calculated Biot values were very low (< 1.0) for all the adsorbents.…”
Section: Model Parameters and Mass Transfer Resistancescontrasting
confidence: 40%
See 1 more Smart Citation
“…By example, Barboza et al [5] and [12] reported values of the Biot in the range of 30 ~ 50 for the adsorption of CA into synthetic resin Amberlit IRA 400. Other authors have related Bi 100 with external mass transfer resistance as a limiting step [17,18]. In this present work, the calculated Biot values were very low (< 1.0) for all the adsorbents.…”
Section: Model Parameters and Mass Transfer Resistancescontrasting
confidence: 40%
“…It is known that increasing the amount of solids in the reactor increased the productivity of the process since there was a decrease in equilibrium time, mainly due to the contact surface of the adsorbent [18]. However, this confirmation is important, since there are cases where the increase in the amount of solids causes a decrease in the adsorption capacity [19].…”
Section: Applicability Of Nax Zeolite To Recovery Clavulanic Acidmentioning
confidence: 99%
“…Layered double hydroxides (LDHs) are widely used for catalysis and sorption and are sinks for the mineralization of insidious anions such as chromates [2,3], selenates [4], fluorides [5], radioactive anions [6], and various organic pollutants [7]. LDHs exhibit anion exchange properties, which make them candidate materials for the immobilization of arsenate in the interlayer region of the LDHs.…”
Section: Introductionmentioning
confidence: 99%
“…They have recently received increasing attention, owing to their versatility and usefulness in a wide range of technological applications such as adsorbents, 8 functional materials, 9 twodimensional solid-state nanoreactors, 10 bioactive nanocomposites, 11 and so on. LDHs can be represented by the general formula [M 2+ 1-x M 3+…”
Section: Introductionmentioning
confidence: 99%